The comparison of levofloxacin- and clarithromycin-based bismuth quadruple therapy regimens in Helicobacter pylori eradication - Abbas Arj; Marzieh Mollaei; Mohsen Razavizadeh; Alireza Moraveji (Wolters Kluwer Medknow Publications, 2020)
Objective: The aim of the current study was to compare the efficacy of quadruple therapy including levofloxacin and clarithromycin for Helicobacter pylori eradication. Methods: This clinical trial study was conducted on 189 patients with H. pylori infection who underwent gastroscopy and stomach biopsy in Shahid Beheshti Hospital, Kashan, Iran. After classification of patients, one group was treated with bismuth subcitrate (120 mg, 2 tablet/12 h), omeprazole (20 mg/12 h), amoxicillin (1 g/12 h), and clarithromycin (500 mg/12 h) and other group with bismuth subcitrate (120 mg, 2 tablet/12 h), omeprazole (20 mg/12h), amoxicillin (1 g/12 h), and levofloxacin (500 mg/12 h) for 2 weeks. After the end of the antibiotic treatment, omeprazole therapy was continued for 4 weeks. Two weeks after discontinuation of omeprazole, fecal antigen test was performed for both the groups to confirm the eradication of H. pylori infection. Findings: The success of H. pylori eradication in the levofloxacin and clarithromycin groups was observed in 78 (89.7%) and 71 (69.6%) patients, respectively (P < 0.01). A significant difference was also seen between the two groups in terms of side effects and its incidence (P < 0.01), so that the incidence of side effect types in the clarithromycin group was more than the levofloxacin group except muscular pain and fatigue (P < 0.01). Conclusion: Levofloxacin-based quadruple regimen therapy was superior to clarithromycin-based quadruple regimens regarding H. pylori eradication and side effects. Therefore, the levofloxacin-based regimen can be considered as an effective treatment for the first-line anti-H. pylori therapy.